1980
DOI: 10.1111/j.1476-5381.1980.tb14563.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cyclic Nucleotides and Related Compounds in Nerve‐mediated Vasodilatation in the Cat Submandibular Gland

Abstract: Intra‐arterial administration of a number of purine compounds to the cat submandibular salivary gland led to an increased blood flow. The threshold concentration of the most potent vasodilators, adenosine 5′‐triphosphate (ATP) and adenosine 5′‐diphosphate (ADP) was about 2 μmol/l. Adenosine and guanosine 5′‐triphosphate (GTP)required about 25 μmol/l, adenosine 3′,5′‐cyclic monophosphate (cyclic AMP) 40 μmol/l, guanosine 5′‐diphosphate (GDP) 125 μmol/l and dibutyryl guanosine 3′,5′ cyclic monophosphate (db cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The vascular escape seen after NA infusions or sympathetic nerve stimulation in normal animals coincides in time with a-receptor mediated release of vasodilatory metabolites, such as adenosine, from effector cells (Fredholm 1976, Fredholm & Hedqvist 1978. Purine compounds including adenosine have also been shown to cause vasodilation in the cat submandibular gland (Jones et al 1980). It has also been reported that /?-adrenoceptor blockade reduces the rapid vasodilation seen after sympathetic nerve stimulation (Bhoola et al 1965).…”
Section: Discussionmentioning
confidence: 99%
“…The vascular escape seen after NA infusions or sympathetic nerve stimulation in normal animals coincides in time with a-receptor mediated release of vasodilatory metabolites, such as adenosine, from effector cells (Fredholm 1976, Fredholm & Hedqvist 1978. Purine compounds including adenosine have also been shown to cause vasodilation in the cat submandibular gland (Jones et al 1980). It has also been reported that /?-adrenoceptor blockade reduces the rapid vasodilation seen after sympathetic nerve stimulation (Bhoola et al 1965).…”
Section: Discussionmentioning
confidence: 99%
“…In experiments designed to test the sodium-dependency of amino acid transport the NaCl and NaHCO3 in the perfusate were removed and replaced by equimolar quantities of buffered Trizma HCl (Sigma). In these experiments 1 mM-adenosine (Sigma) was added to both sodium-free and control perfusates to maintain maximal vasodilatation in the preparation (Jones, Mann & Smaje, 1980). All perfusates were maintained at 37 'C and gassed with 95% 02-5% C02 to a pH of 7 3-7 4.…”
Section: Perfusatesmentioning
confidence: 99%
“…Desensitisation of muscarinic receptors by ATP and 3 0 -O-(4-benzoyl)benzoyl ATP (Bz-ATP) acting on P2X 7 receptors in rat parotid acinar cells has been reported (Fukushi 1999). Intra-arterial administration of various nucleotides, including ATP and ADP to the cat submandibular salivary gland led to increase in blood flow, possible mimicking neurally released ATP as a cotransmitter in parasympathetic and/or sympathetic nerves (Jones et al 1980). Reviews of the distribution and function of P2 nucleotide receptors in salivary glands are available (Novak 2003;Turner et al 1999).…”
Section: Exocrine Glandsmentioning
confidence: 96%